Trends in lipid profile and lipid control among survivors of stroke or myocardial infarction among US adults, 2001–2018 - Dong, Weiwei; Yang, Zhiyong (Frontiers in Endocrinology, 2023)
Background We aim to analyze the change in lipid profile and lipid control among survivors of stroke and/or myocardial infarction among US adults from 2001–2018. Methods In total, 3,736 survivors of stroke and/or myocardial infarction from the 2001–2018 National Health and Nutrition Examination Surveys were included in this study, representing a weighted total population of 110,005,898. Trends for lipid concentration and lipid control rate over time were detected via general linear regression analysis and lipid control was compared by sex and race via survey-weighted logistic regression analysis. Results The total cholesterol, LDL, and triglyceride concentrations were significantly decreased in survivors from the 2001–2002 survey cycle to the 2017–2018 survey cycle (p for trend  0.01). Lipid control was defined as total cholesterol < 200 mg/dL. Among survivors, the lipid control rate increased from 56.2% (95% CI: 43.9%, 67.7%) in the 2001–2002 survey cycle to 73.2% (95% CI: 64.8%, 80.2%) in the 2017–2018 survey cycle (p for trend  0.01). Women had a higher lipid concentration and were more likely have poor lipid control compared to men. Non-Hispanic White survivors possessed better lipid control than other races survivors. Conclusions Lipid concentrations decreased and lipid control improved in stroke and/or myocardial infarction survivors from 2001 to 2018, with heterogeneity observed according to sex and race.